2005
DOI: 10.1093/ageing/afi090
|View full text |Cite
|
Sign up to set email alerts
|

Driving cessation in patients attending a memory clinic

Abstract: Driving cessation was affected not only by psychometric performance but also by demographic and personal factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
6
25
3
4
Order By: Relevance
“…In particular, older age and greater impairment in cognition and function predicted driving cessation in our study. These findings are consistent with those focused on people with dementia, which have similarly found that older age and lower cognition and function predict driving status [17,30,31,32]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, older age and greater impairment in cognition and function predicted driving cessation in our study. These findings are consistent with those focused on people with dementia, which have similarly found that older age and lower cognition and function predict driving status [17,30,31,32]. …”
Section: Discussionsupporting
confidence: 91%
“…This study, however, was limited by its cross-sectional design and small sample. Another study found a relationship between older age and driving cessation, but did not distinguish between MCI and dementia in its analyses [17]. Other research has found a relationship between poorer cognition and driving in older people [18,19], though did not specifically assess this relationship in people with MCI.…”
Section: Introductionmentioning
confidence: 99%
“…COSID findings confirmed the associations previously documented of driving cessation with disease severity, increasing cognitive impairment and age. [4][5][6][7]9 These same factors have also been shown to increase the risk of motor-vehicle collisions in people with dementia. 10 Male gender has been associated with a higher risk of crashes and moving violations; 22 it is notable that at baseline, we found women to be significantly likelier than men to have already quit driving.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 430 patients at a memory clinic, age, an urban dwellingplace, level of cognitive function and relative ability to perform the activities of daily living were found to be predictive of driving cessation. 7 Similarly, in a small prospective study of 53 patients with dementia, age and Mini-Mental State Examination (MMSE) 8 score predicted driving cessation over the next 2-3 years. 9 Determination of the factors associated with driving cessation is important, given the well-documented association between the risk of being involved in a motorvehicle collision and the severity and duration of the dementia.…”
mentioning
confidence: 99%
“…Concerning the effect of DAT on crash risk, certain studies have found a higher crash risk [18][19][20][21][22][23][24] , while others have not [25][26][27] . A higher crash risk is probably not found systematically because people suffering from DAT often limit or even stop driving altogether [19,26,28] , these restrictions increasing with the severity of the disease [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%